Unmasking violations against human dignity in selected Afrikaans films in South Africa 1960-1976 : a practical theological investigation - Van Huyssteen, Elmarie (Stellenbosch : Stellenbosch University, 2017)
Stellenbosch University. Faculty of Theology. Dept. of Practical Theology and Missiology.